REKONSEPTUALISASI GERAKAN DAKWAH JAMAAH TABLIGH KOTA PALOPO - Sulfikar, Achmad (IAIN Palopo, 2016)
AbstractThis study aims to acquire factual knowledge, understanding and expressing a variety ofsymptoms that arise throughout the process of conveying messages of dakwah by members ofJamaah Tabligh Palopo, and develop concepts, theoretical models, and communicationapproaches about the role of Jamaah Tabligh as a preacher. Researchers conducted aparticipant observation of the Jamaah Tabligh Palopo uses a dramaturgical theory of ErvingGoffman, who use the theater metaphor to analyze human behavior. Through this research, willknow what, why and how theyre to preach, especially about their impression management inconveying the messages of dakwah. The author found that Jamaah Tabligh is more of a culturalmovement, the movement well organized. In the context of dramaturgy, there is a clearline between the front stage and backstage, but Jamaah Tabligh gives an opportunity to thepublic to at any time to cross the edge. Actors in this case members of the Jamaah Tabligh triedto play a good role as a preacher; it is dominated by the more spiritual motivation